2014
DOI: 10.1186/s12964-014-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

The Brucella TIR domain containing proteins BtpA and BtpB have a structural WxxxE motif important for protection against microtubule depolymerisation

Abstract: BackgroundThe TIR domain-containing proteins BtpA/Btp1/TcpB and BtpB are translocated into host cells by the facultative intracellular bacterial pathogen Brucella. Here, they interfere with Toll like receptor signalling to temper the host inflammatory response. BtpA has also been found to modulate microtubule dynamics. In both proteins we identified a WxxxE motif, previously shown to be an essential structural component in a family of bacterial type III secretion system effectors that modulate host actin dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 57 publications
8
29
3
Order By: Relevance
“…We found that ectopically expressed TirS accumulated in filament-like structures of irregular shapes within the host cytosol but that do not co-localize with typical cytoskeleton components (microtubules, actin or intermediate filaments). This observation is different from those previously described for other bacterial TIR proteins from Brucella [8,16] and BaTdp from B . anthracis [18].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that ectopically expressed TirS accumulated in filament-like structures of irregular shapes within the host cytosol but that do not co-localize with typical cytoskeleton components (microtubules, actin or intermediate filaments). This observation is different from those previously described for other bacterial TIR proteins from Brucella [8,16] and BaTdp from B . anthracis [18].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to its ability to interfere with TLR signaling, the bacterial TIR effector protein from Brucella BtpA targets and modulates microtubules [16] through a WxxxE motif [17] as well as the recently identified TIR protein from Bacillus anthracis referred to as BaTcp [18]. Since the WxxxE is also present in TirS, we investigated the intracellular localization of ectopically expressed TirS by confocal microscopy on HeLa cells transfected with myc-TirS and indirect immuno-fluorescence staining with anti-myc antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recently the TIR domain of TcpC has been shown to directly interact with the NACHT leucin-rich repeat PYD protein 3 (NLRP3) inflammasome and caspase-1, besides MyD88, to perturb inflammasome activation (Waldhuber et al, 2016). There are also additional potential targets yet to be identified for BtpA/TcpB since it interferes with microtubule dynamics (Radhakrishnan et al, 2011;Felix et al, 2014) and induces unfolded protein response (Smith et al, 2013). The EMBO Journal UBAP1 targeting by Pseudomonas TIR domain protein Paul RC Imbert et al This notion that bacterial TIR domains provide a broad interaction platform is supported by our observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, preferential binding to MyD88 was also demonstrated [16]. It is likely that these Brucella TIR-containing proteins display additional targets or functions, as they modulate microtubule dynamics when ectopically expressed [17, 18] and BtpA was shown to induce the unfolded protein response [19].…”
Section: Introductionmentioning
confidence: 99%